Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah (Sak Emkm) Pada Umkm Toko Beras Barokah - Devina Nurdiana Sudrajat; Etti Ernita Sembiring (Indonesian Accounting Research Journal, 2023)
The lack of knowledge of preparing financial statements are still obstacles so that some companies have not compiled financial reports, for example, Toko Beras Barokah MSMEs. This causes the owner not to know for sure how much profit he gets and the owner has difficulty getting a capital loan from the bank. This study aims to find out how to compile financial reports based on SAK EMKM at Toko Beras Barokah MSMEs. The method used is descriptive quantitative method. The data used were obtained from observations, interviews, and documentation. Based on the results ofthe study, Toko Beras Barokah SMEs have not prepared financial statements according to SAK EMKM. The author prepares the financial report for April 2021 in accordance with SAK EMKM.